Accumulated incidence of falls in people hospitalised with cancer and related factors - Maria Montserrat Martí‐Dillet; Cristina Fernández‐Rodriguez; Aniol Ginesta‐Guanter; Rosa Suñer‐Soler (Wiley, 2023)
Abstract Aim To study the accumulated incidence of falls of people hospitalised with cancer and analyse the related intrinsic and extrinsic factors. Design A prospective study of people hospitalised with cancer at the Catalan Institute of Oncology. Methods Intrinsic factors and extrinsic factors related to the fall have been studied. The data were gathered from the clinical history and a specific adverse events notification programme and patients were followed during hospitalisation. Results A total of 117 of 6090 patients admitted during the period of study were included, with an accumulated incidence of falls of 0.019. Mean age 63.4 years (SD 11.5) and 65.5% men. Patients with lung cancer accounted for 25.6% of the total number of falls, followed by haematological cancer at 24.8%. Most falls were without consequences (71.8%). The data reveal that people hospitalised with cancer are at greater risk of falling, even though the accumulated incidence observed in the present study is low.